Utilización de diferentes tipos de Mezclas Forrajeras en Conejos mejorados y criollos para evaluar el rendimiento productivo en etapa de crecimiento en el CEASA. - Vega Moposita, Erika Alexandra (2019)
In order to obtain information based on the use of diets based on alfalfa, chicory and a homogeneous mixture of the two forages in improved and natural rabbits and to evaluate the productive performance in the growth stage, this research project was carried out for 8 weeks in the CEASA at Cotopaxi Technical University, located between the number 1 house of the rabbits and the number 2 shed of the guinea pigs in individual cages of 0.50 cm of stainless steel adapted for this type of investigation, the place of execution is at 2,870 mals and a temperature of 10 ° C on average. We used a completely randomized bi-factorial block design (DBCA BIFACTORIAL) with 4 treatments and 5 repetitions per treatment divided into two factors. The Factor A that represents the natural rabbits and the Factor B that represents the improved rabbits (New Zealand race), each factor had 20 rabbits randomly distributed at two months of age using a total of 40 rabbits with an initial average weight for Factor A of 578.1 g. and for Factor B of 853.9 g. The following treatments were tested: T0 (control) common mixtures of CEASA, T1 (treatment 1) alfalfa diet, T2 (treatment 2) diet of chicory, T3 (treatment 3) alfalfa diet plus chicory. The analysis of variance was performed through the Bonferroni model at 0.05%. The weights obtained in the investigation for week 8 in the case of Creole rabbits in the growth stage were 1219.4 g of the Control, 1510.2 g of Treatment 1, 1340.6 g. in Treatment 2, 1247.2 g. obtained in Treatment 3, so the average obtained from the treatments in the last week was 1329.35 g., resulting in a Coefficient of Variation of 63.95% without presenting significant difference of (Pvalue 0.5926), while the weights of rabbits Improved in week 8 showed values of 2442.4 g. for the Control, Treatment 1 with a value of 1366 g., Treatment 2 obtained a weight of 1536.6 g., while for Treatment 3 a weight of 1594 g., the average of the treatments of this week was 1734.75 g., according to the analysis of variance (Pvalue is 0.5926) with a Coefficient of Variation of 63.95%. It is observed that the diet that shows greater predilection and greater representativeness in weight gain and feed conversion is the alfalfa-based diet followed by mixtures of alfalfa plus chicory as highly nutritious plants allow rabbits to meet their nutritional needs required at this stage of growth. Concluding that it is viable to use chicory as an alternative diet in the feeding of rabbits and mix it with a legume.